Retrospective Analysis on Sutures Used for Open Method Extraction in Patients Attending A Private Dental Institution - KRISNAMALAY, KAUSALYAH; R.N, BALAKRISHNAN; KUMAR.V, JAYANTH (The journal of contemporary issues in business and government, 2021)
Procedure for open method extraction, initially starts with giving local anaesthesia injection and followed by incisions and flap design. Sutures are defined as stitches or series of stitches made to secure apposition of the edges of a surgical or traumatic wound. It is also defined as any strand or material utilized to ligate blood vessels or approximate tissues. To determine the presences of sutures in open method extraction The purpose of the study was to assess the sutures in open method extraction (post operatively). A study was carried out by collecting data by reviewing patients data and analysing the data of 86000 patients between June 2019 and March 2020 at the private dental institute. The sample size that was taken is 292 patients who came to the private dental institute for consultation. The case sheets of those patients were reviewed for presence or absence of sutures post operative to open method extraction. Data was statistically analysed using SPSS 2.0, Chi-Square Test was conducted. Result was recorded. Majority of the dental students used suturing as the wound closure for post operative open method extraction procedure. Within the limitation of the study, male patients were predominant and suture was present in majority cases of post open method extraction. And the most common site which underwent open method extraction was tooth number 48 and 38 ( lower third molars).